Applying the principles of green chemistry in art: design of a cross-disciplinary course about 'art in the Anthropocene: greener art through greener chemistry'. Issue 2 (3rd April 2019) - Marteel-Parrish, Anne; Harvey, Heather
ABSTRACT: This cross-disciplinary course bridging the disciplines of art and chemistry provides an exceptional environment in which first-year students and beyond are engaged and challenged in new ways. This dual lab/studio-based course, titled "Art in the Anthropocene: Greener Art through Greener Chemistry, " enables students to use their imagination, creativity, and innovation to respond to environmental issues and concerns through art. Students are asked to reflect on the nature and implications of the actual physical materials that artists use and to achieve a renewed sense of social and ethical responsibility through the content of their artwork. The curriculum is designed so that teachers guide students on how chemical processes are used to make art materials in an environmentally friendly way. The overall goal is to apply green chemistry principles in the making of artworks that can be crafted with reclaimed, recycled, and naturally available materials, non-toxic solvents and paints, and using sustainable forms of energy while keeping ethical values in mind. GRAPHICAL ABSTRACT: